A multi-criteria decision making for intercrop selection in RISDA Rubber Plantation / Intan Norfazilah Zakri, Nurul Najiha Hasan Basri and Suroh Artini Mahsun - Zakri, Intan Norfazilah; Hasan Basri, Nurul Najiha; Mahsun, Suroh Artini (2019)
Selecting the appropriate intercrop for the rubber field offers land usage with high efficiency. It can bring benefit ouring the waiting period for rubber to grow. Analytical Hierarchy Process (AHP) is an effective Multi-Criteria Decision Making Method (MCDM) which provides a rank of suitable intercrop. The objectives of this study are to determine the priority of intercropping criteria and to determine the most suitable intercrop in RISDA rubber plantation. In this research, the application of AHP was implemented in one of the RISDA rubber plantation in Kampung Kuala Sawah, Rantau, Negeri Sembilan. The decision problem was structured into a three-level hierarchy using the AHP. The criteria of the decision were arranged in hierarchical structures and the judgments were made by experts. There are four criteria that have been finalized in selecting the best intercrop in rubber plantation which are soil fertility, selling rate per kilogram, growth rate and weather adaption. Besides that, pair-wise comparisons allowed for accurate subjective criteria weighting. The result showed the suitability of each intercrop which are watermelon, banana, and pineapple. The result from the study showed that among the four criteria in selecting the intercrop, the most important criterion in RISDA is the growth rate. This is followed by soil fertility, weather adaption and selling rate per kilogram, respectively. Watermelon is recommended as the most suitable intercrop at RISDA rubber plantation.